Body surface area is a predictor of maturity status in school children and adolescents - Fernando Alvear-Vasquez; Rubén Vidal-Espinoza; Rossana Gomez-Campos; Luis Felipe Castelli Correia de Campos; Evandro Lazari; Jose Francisco Guzmán-Luján; Ana Pablos-Monzó; Marco Cossio-Bolaños (BMC, 2023)
Abstract Background Generally, Body surface area (BSA) changes significantly during growth and maturation. These increases portend a possible relationship between body size as determined by BSA with maturational status in children and adolescents. Objective To determine the relationship between maturity status (MS) obtained by non-invasive anthropometric methods and body surface area (BSA) in children and adolescents of both sexes in a regional population of Chile. Additionally, we sought to verify the type of linear or nonlinear relationship between MS and BSA in both sexes. Methods A descriptive (cross-sectional) study was designed in 950 children and adolescents of both sexes (539 males and 411 females). The age range ranged from 6.0 to 17.9 years. Anthropometric measurements were evaluated: body weight, standing height, sitting height. MS was assessed by means of two non-invasive anthropometric techniques. Both techniques predict peak years of growth velocity (APHV) through a regression equation for each sex. BSA (m2) was estimated by means of the Haycock equation. Results The R2 in the linear model is relatively lower (R2 = 0.80 to 0.89 in males and 0.74 to 0.66 in females) in relation to the nonlinear quadratic model (R2 = 0.81 in males and 0.76 to 0.69). The quadratic nonlinear quadratic model reflected an adequate fit (RMSE) for the data set, being in men (RMSE = 1.080 and 1.125), while in women (RMSE = 1.779 and 1.479). Conclusion BSA is positively associated with MS determined by two non-invasive methods in Chilean children and adolescents: The nonlinear quadratic model was a better fit to the data distribution. The results suggest the use of BSA as a possible predictor of maturity status in Chilean youth.